PENGARUH ALAT BELAJAR TERHADAP MOTIVASI BELAJAR WARGA BELAJAR PENDIDIKAN KESETARAAN - Hasrindah Indah; Rudi Amir Rudi; Fatmawati Gaffar Fatma (UNIVERSITAS NEGERI MAKASSAR, 2023)
ABSTRACTThe problem in this study is whether there is an effect of the influence of learning tools on the learning motivation of citizens learning equality education at PKBM Insan Fauziah, Lamuru Village, Matausu District, Bombana Regency. This research uses a quantitative research approach with a survey research type. The population in this study were 68 people who studied equality education, and the research sample was taken from the entire population of 68 people. Methods of data collection using questionnaires and documentation. The data analysis method used is descriptive statistical analysis, simple linear regression test. The results of the research are that there is an effect of learning tools on the learning motivation of citizens learning equality education in PKBM Insan Fauziah, Lamuru Village, Matausu District, Bombana Regency. Learning tools have an influence on the learning motivation of learning citizens because with the existence of learning tools they feel they can measure learning well. Doubts that often arise in learning residents to take part in learning are due to feeling that the learning tools they have are incomplete, resulting in them being unmotivated in learningÂ Learning Tools, Learning Motivation, Equality Education